Social and cultural inclusion in university education in Ancash (Peru) - Julca Guerrero, Félix (2023)
The study analyzes the policies of social and cultural inclusion in universities in Ancash, Peru. Socioculturally, Ancash has always been diverse; currently, ancestral cultural traditions are still in practice, and there are more than 500,000 Quechua speakers. There are five universities in Ancash, two public universities with degrees and three private universities, one with degrees and two without. A descriptive cross-sectional study was carried out. The results report that only one public university carries out two initial actions of sociocultural inclusion with an intercultural perspective: the incorporation of Quechua and some Andean culture topics in the curriculum, and the access of students from rural communities to the university through a special admission exam. However, intercultural teachers do not have the required profile. Thus, Ancash universities show a lack of greater commitment and coherence with the sociocultural and sociolinguistic diversity of the region and the country. Therefore, innovative, reflective, inclusive and intercultural universities are needed to train competent human resources in, with and for diversity.